Special Service Management of School Cafeteria at Junior High School 13 Malang - Sari, Intan; Timan, Agus; Kusumaningrum, Desi Eri (Universitas Negeri Malang, 2024)
School cafeteria is a special service that provides healthy food and drinks for students and school staff who occupy a building part of the school building. The cafeteria is one form of school attention to the school community in order to meet their needs. The purpose of this study was to determine how the canteen is managed in schools. The method used is a qualitative approach with interview and observation techniques. The results of this study are that schools implement POAC management in managing school canteens.